Effect Of Career Development, Motivation And Self Efficacy On Employee Performance At Pt. Pln Palopo Branch - Dewi Sartika; Muhammad Aqsa (Jurnal Mantik, 2022)
Human resources as an important part of the sustainability of a company need to get the right portion in the process of running the company. Human capital supported by a good career development process, high motivation and convincing self-efficacy will have good implications for the company. This study aims to determine and analyze the influence of career development, motivation and self-efficacy on employee performance. This research was conducted on employees of PT. PLN Palopo Branch by distributing questionnaires as a data collection method. With a total sample of 77 respondents. The results of the study partially show that career development has a significant effect on performance. Likewise, motivation and self-efficacy have a significant effect on employee performance at PT. PLN Palopo Branch.